2011
DOI: 10.1136/gut.2010.224329
|View full text |Cite
|
Sign up to set email alerts
|

Long-term peptic ulcer rebleeding risk estimation in patients undergoing haemodialysis: a 10-year nationwide cohort study

Abstract: ESRD patients had higher long-term risk of peptic ulcer rebleeding, especially in certain populations. The enhanced risk gradually decreased after the first year and stabilised after the fifth year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 22 publications
4
41
1
1
Order By: Relevance
“…Previous studies have indicated that patients undergoing dialysis are at particular risk for recurrence of upper GI bleeding. 2,4 Although upper GI bleeding frequently complicates the course of patients already hospitalized, the management of episodes that begin in the ambulatory setting does not necessarily mandate admission. Almost 40% of upper GI bleeding episodes in Medicare patients were managed in the outpatient setting, 14 and 20% of these episodes recurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that patients undergoing dialysis are at particular risk for recurrence of upper GI bleeding. 2,4 Although upper GI bleeding frequently complicates the course of patients already hospitalized, the management of episodes that begin in the ambulatory setting does not necessarily mandate admission. Almost 40% of upper GI bleeding episodes in Medicare patients were managed in the outpatient setting, 14 and 20% of these episodes recurred.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have indicated that patients requiring dialysis are particularly prone to developing upper gastrointestinal (GI) bleeding, with subsequent poor outcomes. [2][3][4] In the general (non-ESRD) population, the incidence of, and mortality associated with, acute nonvariceal upper GI bleeding has been declining over time. [5][6][7][8][9][10][11] It is unknown, however, whether the ESRD population has experienced similar changes in rates or complications of this bleeding event and its outcomes.…”
mentioning
confidence: 99%
“…Using the Taiwan National Health Insurance Research Database (NHIRD), Wu et al found that patients with ESRD had a high long-term risk of developing peptic ulcer re-bleeding, especially in those taking ulcerogenic drugs or who also had H. pylori infection, ischemic heart disease, or liver cirrhosis. 11 However, the long-term risk of UGIB mortality in patients with uremia remained unclear. Therefore, this study aimed to investigate the association between mortality and UGIB in patients with uremia in order to realize the true incidence of mortality caused by UGIB and estimate the in-hospital mortality risk of UGIB in patients with uremia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ESRD exhibit higher rates of rebleeding (up to 40.6% in study by Cheung et al [32]), as well as increased delayed rebleeding (beyond seven days) (16,33). ESRD has also been associated with increased long-term peptic ulcer rebleeding (34).…”
Section: Other Biasmentioning
confidence: 99%